DRYMATTER PARTITIONING AND GRAIN YIELD POTENTIAL OF MAIZE-CHICKPEA SEQUENCE AS INFLUENCED BY SOWING TIME AND NITROGEN LEVELS - M. RATNAM (The Journal of Research ANGRAU, 2016)
A field experiment was conducted on clay soils of Regional Agricultural Research Station, Lam, Guntur during kharif and rabi of 2013-14 & 2014-15 to find out the influence of sowing windows and nitrogen levels on drymatter partitioning and yield potential of maize-chickpea sequence under rainfed agro-climatic condition of Krishna zone. Sowing time and nitrogen levels were significantly influenced the drymatter accumulation at all growth stages and yield of preceding maize and succeeding chickpea under of maize-chickpea sequence. Higher drymatter accumulation and yield of preceding maize was recorded when maize sown on the 2nd FN of June with 200 % RDN and the more drymatter partitioning and grain yield of succeeding chickpea was recorded when preceding maize sown on 1st FN of July with 200 % RDN followed by 100 % RDN applied to succeeding chickpea during both the years of the experimentation.